Battery cells, batteries and electrical devices
By optimizing the thickness and porosity of electrode material layers and the separator in battery cells, the battery cells achieve high rate and power performance, addressing the limitations of current battery technologies.
Patent Information
- Application Number
- JP2024561620
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-10-14
- Publication Date
- 2025-05-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Current battery technologies struggle to achieve both high rate and power performance, as they often exhibit large resistance at high rates, failing to meet market demands.
The development of battery cells with specific relationships between the thickness and porosity of the positive and negative electrode active material layers, the separator, and the electrolyte, which enhance ion transmission and reduce resistance, thereby improving power performance.
The optimized battery cells achieve high rate and low resistance, leading to improved power performance and the ability to meet both rate and power performance requirements.
Smart Images

Figure 2025514727000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of batteries, and in particular to battery cells, batteries and electrical devices. [Background technology]
[0002] With the rapid development of battery technology, batteries are widely used in electric devices such as vehicles. At present, the market has high requirements for the rate performance and power performance of batteries. However, in related technologies, batteries cannot achieve both rate performance and power performance. Summary of the Invention
[0003] The present application provides a battery cell, a battery, and an electric device that can achieve both rate performance and power performance.
[0004] According to a first aspect, an embodiment of the present application provides a battery cell including a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer provided on at least one side of the positive electrode current collector. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer provided on at least one side of the negative electrode current collector. A separator is provided between the positive electrode plate and the negative electrode plate. The positive electrode active material layer, the negative electrode active material layer, the separator, and the electrolyte satisfy the following relationship:
number
[0005] In the battery cell provided by the embodiments of the present application, the positive electrode active material layer, the negative electrode active material layer, the separator and the electrolyte satisfy the above-mentioned relationship, which contributes to the transmission of ions in the battery cell, allows the battery cell to have low resistance at a high rate, and further improves the power performance of the battery cell, thereby achieving both the rate performance and power performance of the battery cell.
[0006] In some embodiments of the present application, the thickness T1 of the positive electrode active material layer satisfies 0.0035 cm≦T1≦0.0055 cm, and optionally satisfies 0.0035 cm≦T1≦0.0045 cm. By setting the thickness T1 of the positive electrode active material layer within the above appropriate range, the transmission path of ions in the positive electrode active material layer can be shortened, the resistance of the battery cell can be further reduced, and the power performance of the battery cell can be improved.
[0007] In some embodiments of the present application, the porosity P1 of the positive electrode active material layer satisfies 30%≦P1≦60%, and optionally satisfies 40%≦P1≦60%. Setting the porosity P1 of the positive electrode active material layer within the above appropriate range is favorable for the transmission of ions in the positive electrode active material layer, and can further reduce the resistance of the battery cell and improve the power performance of the battery cell.
[0008] In some embodiments of the present application, the positive electrode active material layer has a BET specific surface area S1 of 8 m 2 / g≦S1≦12m 2 / g. By setting the BET specific surface area S1 of the positive electrode active material within the above appropriate range, the transmission speed of ions in the positive electrode active material layer can be increased, and the power performance of the battery cell can be further improved.
[0009] In some embodiments of the present application, the thickness T2 of the negative electrode active material layer satisfies 0.003 cm≦T2≦0.005 cm, and optionally satisfies 0.0035 cm≦T2≦0.005 cm. By setting the thickness T2 of the negative electrode active material layer within the above appropriate range, the transmission path of ions in the negative electrode active material layer can be shortened, the resistance of the battery cell can be further reduced, and the power performance of the battery cell can be improved.
[0010] In some embodiments of the present application, the porosity P2 of the negative electrode active material layer satisfies 30%≦P2≦60%, and optionally satisfies 40%≦P2≦60%. Setting the porosity P2 of the negative electrode active material layer within the above appropriate range is favorable for the transmission of ions in the negative electrode active material layer, and can further reduce the resistance of the battery cell and improve the power performance of the battery cell.
[0011] In some embodiments of the present application, the negative electrode active material layer has a BET specific surface area S2 of 1.7 m 2 / g≦S2≦2.2m 2 / g. By setting the BET specific surface area S2 of the negative electrode active material within the above appropriate range, the transmission speed of ions in the negative electrode active material layer can be increased, and the power performance of the battery cell can be further improved.
[0012] In some embodiments of the present application, the thickness T3 of the separator satisfies 0.0005 cm≦T3≦0.0015 cm. By setting the thickness T3 of the separator within the above range, the transmission path of ions in the separator can be shortened, the resistance of the battery cell can be further reduced, and the power performance can be improved.
[0013] In some embodiments of the present application, the porosity P3 of the separator satisfies 30%≦P3≦80%. Setting the porosity P3 of the separator within the above range is favorable for ion transmission, and can increase the ion transmission speed, reduce the resistance of the battery cell, and improve the power performance of the battery cell.
[0014] In some embodiments of the present application, the separator has an air permeability of 150s / 100cm 3 Setting the separator's air permeability within the above range is advantageous for ion transmission, making it possible to increase the ion transmission speed, further reducing the resistance of the battery cell, and improving the power performance of the battery cell.
[0015] In some embodiments of the present application, the ionic conductivity G of the electrolyte at 25° C. satisfies 13 mS / cm≦G≦26 mS / cm, and optionally satisfies 14 mS / cm≦G≦25 mS / cm. By setting the ionic conductivity G of the electrolyte at 25° C. within the above appropriate range, the conductive ability of ions in the electrolyte can be enhanced, the resistance of the battery cell can be further reduced, and the power performance of the battery cell can be further improved.
[0016] In some embodiments of the present application, the electrolyte retention rate N satisfies 3 g / Ah≦N≦7 g / Ah. By setting the electrolyte retention rate N within the above range, the resistance of the battery cell can be reduced, improving the power performance of the battery cell and further improving the cycle performance of the battery cell.
[0017] In some embodiments of the present application, the electrolyte solution includes an electrolyte salt and an organic compound having a viscosity μ of 0.1 mPa·s to 3.5 mPa·s. By including an electrolyte salt and an organic compound having a viscosity μ that satisfies the above relationship in the electrolyte solution, the electrolyte solution has high conductivity, and can further reduce the resistance of the battery cell and further improve the power performance of the battery cell.
[0018] In some embodiments of the present application, based on the mass of the electrolyte solution, the mass fraction A of the electrolyte salt satisfies 10%≦A≦20%, and the mass fraction B of the organic compound satisfies 30%≦B≦70%. By setting the mass fraction A of the electrolyte salt and the mass fraction B of the organic compound within the above appropriate ranges, respectively, the viscosity of the electrolyte solution can be reduced, the conductivity of the electrolyte solution can be improved, and the resistance of the battery cell can be further reduced and the resistance of the battery cell can be further improved.
[0019] In some embodiments herein, the electrolyte salt comprises a lithium salt, and optionally the lithium salt is selected from lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide, or a combination thereof.
[0020] In some embodiments of the present application, the organic compound having low viscosity includes a sulfone-based organic compound, an ether-based organic compound, an ester-based organic compound, and a nitrile-based organic compound. Optionally, the sulfone-based organic compound is selected from dimethyl sulfoxide. Optionally, the ether-based organic compound is selected from ethylene glycol dimethyl ether. Optionally, the ester-based organic compound is selected from methyl formate, ethyl formate, methyl acetate, ethyl acetate, methyl acrylate, or a combination thereof. Optionally, the nitrile-based organic compound is selected from acetonitrile.
[0021] In some embodiments of the present application, the electrolyte further comprises a high temperature additive, and the mass fraction C of the high temperature additive satisfies 0.01%≦C≦1% based on the mass of the electrolyte. The high temperature additive and its content can contribute to forming a protective layer on the surface of the plate. The protective layer can be stable under high temperature conditions and is further beneficial to protect the plate, so that the battery cell can have good high temperature performance.
[0022] In some embodiments of the present application, the high temperature additive is selected from lithium tetrafluoroborate, lithium difluorophosphate, lithium fluorosulfonate, lithium sulfamate, or a combination thereof, which contributes to the formation of an inorganic protective layer, and can improve the mechanical strength of the protective layer and further improve the high temperature performance of the battery.
[0023] In some embodiments of the present application, the electrolyte further comprises a film-forming additive, and the mass fraction D of the film-forming additive satisfies 1%≦D≦5% based on the mass of the electrolyte. The film-forming additive and its content can contribute to improving the stability of the interfacial film and improve the cycle performance of the battery cell.
[0024] In some embodiments herein, the film-forming additive is selected from vinylene carbonate, fluorinated ethylene carbonate, vinyl ethylene carbonate, or combinations thereof.
[0025] According to a second aspect, an embodiment of the present application provides a battery, comprising a battery cell according to any one of the embodiments of the first aspect of the present application.
[0026] According to a third aspect, an embodiment of the present application provides an electric device including a battery cell according to any one of the embodiments of the first aspect of the present application, or a battery according to any one of the embodiments of the second aspect of the present application. [Brief description of the drawings]
[0027] In order to more clearly describe the embodiments of the present application, the following briefly describes the necessary drawings used in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can further obtain other drawings according to the drawings without creative labor.
[0028] [Figure 1] 1 is a schematic diagram of a vehicle according to some embodiments of the present application;
[0029] [Diagram 2] 1 is a schematic diagram of a battery pack provided by some embodiments of the present application;
[0030] [Diagram 3] In FIG. 2 an exploded view of the battery is shown.
[0031] [Figure 4] 1 is a schematic diagram of a battery cell according to some embodiments of the present application;
[0032] [Diagram 5] An exploded view of the battery cell in FIG. 4 is shown.
[0033] In the drawings, the drawings are not drawn to scale.
[0034] Symbols:
[0035] 1000 vehicles
[0036] 100 batteries 200 Controller 300 Motor
[0037] 10. Chassis 11 First cabinet 12 Second cabinet
[0038] 20 Battery Cells 21 cases 22 Electrode Assembly 23 Cover Assembly DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] The following detailed description of the present application is given with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the present application, and are merely examples, which cannot limit the scope of protection of the present application.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs. The terms used herein are merely for the purpose of describing the specific examples and are not intended to limit the present application. The terms "include", "have" and any variations thereof in the specification, claims and above description of the drawings of this application are intended to cover a non-exclusive inclusion.
[0041] In some embodiments of the present application, the technical terms "first", "second", etc. are intended only to distinguish different objects and should not be understood to indicate or imply a relative importance, or to imply a number, a particular order, or a hierarchical relationship of the indicated technical features. In some embodiments of the present application, unless otherwise expressly and specifically limited, "plurality" means two or more.
[0042] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in accordance with the embodiment may be included in at least one embodiment of the present application. The various occurrences of the phrase in the specification do not necessarily refer to the same embodiment, nor are they mutually exclusive separate or alternative embodiments. It is expressly and implicitly understood by the artisan that the embodiments described herein can be combined with other embodiments.
[0043] In some embodiments of the present application, the term "and / or" is merely used to describe the relationship between related objects, and indicates that three types of relationships can exist. For example, A and / or B can indicate three cases: A exists alone, A and B exist simultaneously, and B exists alone. In addition, in this specification, the character " / " generally indicates that the related objects before and after it are in an "or" relationship.
[0044] It is obvious to those skilled in the art that various modifications and variations are possible in the present application without departing from the scope of protection of the present application. Therefore, the present application is intended to cover the modifications and variations of the present application that fall within the scope of the corresponding claims (claimed scope) and their equivalents. In addition, the embodiments provided in the present application may be combined with each other if they are not inconsistent.
[0045] Before describing the scope of protection provided by the embodiments of the present application, the present application first details the problems existing in the related art in order to facilitate understanding of the embodiments of the present application.
[0046] Batteries have characteristics such as high power, charge / discharge capability, and high cycle performance, and are therefore widely used in electric devices such as vehicles. Currently, there is a growing demand in the market for the rate and power performance of batteries. However, in conventional technologies, batteries have a large resistance at high rates, and therefore their power performance cannot meet the requirements. For this reason, it is necessary to develop a battery that can achieve both rate and power performance as soon as possible.
[0047] In view of this, embodiments of the present application provide a battery cell, a battery, and an electric device that can achieve both rate performance and power performance.
[0048] Electrical equipment
[0049] In the present application, the electric device may be a mobile phone, a portable device, a notebook computer, a steamer, a spacecraft, a vehicle, an electric toy, an electric tool, etc. The vehicle may be a fuel vehicle, a gas-fueled vehicle, or a new energy vehicle, and the new energy vehicle may be a battery-powered electric vehicle, a hybrid vehicle, or a range-extended electric vehicle, etc. The spacecraft includes an airplane, a rocket, a space shuttle, a spaceship, etc. The electric toy includes a stationary or mobile electric toy, such as a game console, an electric car toy, an electric steamer toy, and an electric airplane toy, etc. The electric tool includes a metal cutting electric tool, a polishing electric tool, an assembly electric tool, and a railway electric tool, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an electric impact drill, a concrete vibrator, and an electric plane, etc. The embodiment of the present application is not particularly limited to the above electric device.
[0050] In the following embodiment, for convenience of explanation, an electric device according to an embodiment of the present application will be described as a vehicle 1000 as an example.
[0051] Please refer to Fig. 1. Fig. 1 shows a schematic configuration diagram of a vehicle provided by some embodiments of the present application.
[0052] As shown in FIG. 1, the vehicle 1000 may be a fuel vehicle, a gas fuel vehicle, or a new energy vehicle, and the new energy vehicle may be a battery electric vehicle, a hybrid vehicle, or a range extender electric vehicle, etc. A battery 100 is provided inside the vehicle 1000, which may be installed at the bottom, front, or rear of the vehicle. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be an operating power source for the vehicle 1000. The vehicle 1000 may further include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for the start, navigation, and operating power needs during driving of the vehicle 1000.
[0053] In some embodiments of the present application, the battery 100 can not only serve as the operating power source for the vehicle 1000, but can also replace or partially replace fuel or natural gas as the driving power source for the vehicle 1000 to provide driving power for the vehicle 1000.
[0054] battery
[0055] Please refer to Figures 2 and 3. Figure 2 shows a schematic diagram of a battery provided by some embodiments of the present application. Figure 3 shows an exploded view of the battery in Figure 2.
[0056] A battery 100 in this application is shown to include at least one battery cell 20. As shown in Figures 2 and 3, the battery 100 includes a housing 10 and the battery cell 20 housed in the housing 10.
[0057] In particular, the housing 10 is used to provide a storage space for the battery cells 20, and may have a plurality of structures. In some embodiments, the housing 10 may include a first housing 11 and a second housing 12, and the first housing 11 and the second housing 12 are engaged with each other to jointly define a storage space for accommodating the battery cells 20. The second housing 12 may be a hollow structure with an opening at one end, and the first housing 11 may be a plate-like structure, and the first housing 11 is engaged with the opening side of the second housing 12 so that the first housing 11 and the second housing 12 jointly define the storage space. The first housing 11 and the second housing 12 may all be hollow structures with an opening at one end, and the opening side of the first housing 11 is engaged with the opening side of the second housing 12. Of course, the housing 10 formed by the first housing 11 and the second housing 12 may have a plurality of shapes, such as a cylinder, a rectangle, etc.
[0058] The battery 100 may include a plurality of battery cells 20. The plurality of battery cells 20 may be connected in series, in parallel, or in series-parallel. A series-parallel connection means that the plurality of battery cells 20 may be connected in series or in parallel. The plurality of battery cells 20 may be directly connected in series, in parallel, or in series-parallel, and the entire configuration of the plurality of battery cells 20 may be housed in the housing 10.
[0059] In particular, each battery cell 20 may be a secondary battery cell or a primary battery, such as, but not limited to, a lithium ion secondary battery cell, a sodium ion secondary battery cell, a magnesium ion secondary battery cell, or a potassium ion secondary battery cell. The battery cells 20 may be cylindrical, flat, rectangular, or have other shapes.
[0060] Battery Cell
[0061] An embodiment of the present application provides a battery cell including a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer provided on at least one side of the positive electrode current collector. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer provided on at least one side of the negative electrode current collector. The separator is provided between the positive electrode plate and the negative electrode plate. The positive electrode active material layer, the negative electrode active material layer, the separator, and the electrolyte satisfy the following relationship:
number
[0062] The positive electrode current collector may have a positive electrode active material layer on one surface, or may have a positive electrode active material layer on two surfaces, or the positive electrode active material and the surface of the positive electrode current collector may not be in contact with each other, and an isolation layer may be provided between the surface of the positive electrode current collector and the positive electrode active material layer, but this is not particularly limited in the embodiment of the present application. The negative electrode current collector may have a negative electrode active material layer on one surface, or may have a negative electrode active material layer on two surfaces, or an isolation layer may be provided between the surface of the negative electrode current collector and the negative electrode active material layer, but this is not particularly limited in the embodiment of the present application.
[0063] In this application, the thickness T1 of the positive electrode active material layer is the thickness of a single-sided positive electrode active material layer, and the thickness T2 of the negative electrode active material layer is also the thickness of a single-sided negative electrode active material layer.
[0064] Porosity is the percentage of the pore volume inside the material to its total volume, and can be tested according to the method of GB / T 24586-2009.
[0065] The ionic conductivity G of the electrolyte is the conductivity of the electrolyte at 25° C. and can be tested by methods well known in the art. The test instrument used can be a REX conductivity meter.
[0066] In the battery cell provided by the embodiment of the present application, the inventor unexpectedly found through experiments that the real ion transmission path is not only related to the thickness of the active material layer and the thickness of the separator, but also related to the porosity of the active material layer and the porosity of the separator. Therefore, in the embodiment of the present application, the real ion transmission path in each layer is closer to the thickness of each layer and its porosity ratio. That is, the thickness T1 and porosity P1 of the positive active material layer, the thickness T2 and porosity P2 of the negative active material layer, the thickness T3 and porosity P3 of the separator, and the ionic conductivity G of the electrolyte satisfy the above relationship, which contributes to the transmission of ions in the battery cell, and the battery cell can have low resistance at high rate, and further improve the power performance of the battery cell, thereby achieving both the rate performance and power performance of the battery cell.
[0067] In some embodiments of the present application, the thickness T1 of the positive electrode active material layer satisfies 0.0035 cm≦T1≦0.0055 cm.
[0068] In these above-mentioned embodiments, by setting the thickness T1 of the positive electrode active material layer within the above-mentioned appropriate range, the transmission path of ions in the positive electrode active material can be shortened, the resistance of the battery cell can be further reduced, and the power performance of the battery cell can be improved.
[0069] In some other embodiments of the present application, the thickness T1 of the positive electrode active material layer satisfies 0.0035 cm≦T1≦0.0045 cm. In this way, the transmission path of ions in the positive electrode active material layer can be further shortened, and the power performance of the battery cell can be further improved, and at the same time, the cycle performance of the battery cell can be improved.
[0070] In some examples, the thickness T1 of the positive electrode active material layer can be, but is not limited to, 0.0035 cm, 0.0036 cm, 0.0037 cm, 0.0038 cm, 0.0039 cm, 0.0040 cm, 0.0041 cm, 0.0042 cm, 0.0043 cm, 0.0044 cm, 0.0045 cm, 0.0046 cm, 0.0047 cm, 0.0048 cm, 0.0049 cm, 0.0050 cm, 0.0051 cm, 0.0052 cm, 0.0053 cm, 0.0054 cm, or 0.0055 cm.
[0071] In some embodiments of the present application, the porosity P1 of the positive electrode active material layer satisfies 30%≦P1≦60%.
[0072] In these above-mentioned embodiments, the porosity P1 of the positive electrode active material layer is set to the above-mentioned appropriate range, which is favorable for the transmission of ions in the positive electrode active material, and the resistance of the battery cell can be further reduced, and the power performance of the battery cell can be improved.
[0073] In some other embodiments of the present application, the porosity P1 of the positive electrode active material layer satisfies 40%≦P1≦60%, thus further increasing the ion transmission rate in the positive electrode active material layer, further reducing the resistance of the battery cell, and improving the power performance of the battery cell.
[0074] In some examples, the porosity P1 of the positive electrode active material layer may be, but is not limited to, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, or 60%.
[0075] In some embodiments of the present application, the positive electrode active material layer has a BET specific surface area S1 of 8 m 2 / g≦S1≦12m 2 / g.
[0076] The BET specific surface area is a well-known term in the art and can be calculated by the BET (Brunauer Emmett Teller) method using a nitrogen gas adsorption specific surface area analysis method. In particular, the nitrogen gas adsorption specific surface area analysis method can be performed using a Tri Star II type specific surface and porosity analyzer manufactured by Micromeritics, Inc., USA.
[0077] In the above-mentioned embodiments, the BET specific surface area S1 of the positive electrode active material is set in the above-mentioned suitable range, which not only increases the ion transmission speed in the positive electrode active material layer and further improves the power performance of the battery cell, but also reduces the contact area between the positive electrode active material and the electrolyte. Even under high voltage or strong oxidizing action, the side reaction of the electrolyte on the surface of the positive electrode active material is reduced, and the gas generation and heat generation are reduced, so that the safety performance and cycle performance of the battery cell are improved.
[0078] In some embodiments of the present application, the positive electrode active material may include materials such as lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds, or combinations thereof. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials in batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (abbreviated as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (abbreviated as NCM211), LiNi0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM811), lithium nickel cobalt aluminum oxide (e.g. LiNi 0.85 Co 0.15 Al 0.05 Examples of lithium-containing phosphates having an olivine structure may include, but are not limited to, lithium iron phosphate (e.g., LiFePO (which may be abbreviated as LFP)), a composite of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO), a composite of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite of lithium manganese iron phosphate and carbon, or a combination thereof.
[0079] In addition, in some embodiments of the present application, the positive electrode active material layer may further include a conductive agent and an adhesive. The embodiments of the present application do not specifically limit the types of conductive agent and adhesive in the positive electrode active material layer, and may be selected according to actual requirements. For example, the conductive agent may be one or more of graphite, superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, but is not limited thereto. The adhesive may be one or more of styrene butadiene rubber (SBR), water-based acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), ethylene-vinyl acetate copolymer (EVA), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylic resin, and polyvinyl alcohol (PVA), but is not limited thereto.
[0080] In some embodiments of the present application, the positive electrode current collector can be made of a material such as a metal foil or a porous metal plate. For example, the material of the positive electrode current collector can be, but is not limited to, a foil or a porous plate of a metal such as copper, nickel, titanium, or silver, or an alloy thereof. Furthermore, in some specific embodiments of the present application, the positive electrode current collector is made of aluminum foil.
[0081] The positive electrode plate of the present application can be manufactured by a method commonly used in the art. For example, a positive electrode active material, a conductive agent, and an adhesive are mixed in a certain mass ratio with an appropriate amount of NMP by thorough stirring to form a uniform positive electrode slurry, and the positive electrode slurry is applied to the surface of an aluminum foil of a positive electrode current collector, and then dried, cold pressed, and cut to obtain a positive electrode plate.
[0082] In some embodiments of the present application, the thickness T2 of the negative electrode active material layer satisfies 0.003 cm≦T2≦0.005 cm.
[0083] In these above-mentioned embodiments, by setting the thickness T2 of the negative electrode active material layer within the above-mentioned appropriate range, the transmission path of ions in the negative electrode active material layer can be shortened, the resistance of the battery cell can be further reduced, and the power performance of the battery cell can be improved.
[0084] In some other embodiments of the present application, the thickness T2 of the negative electrode active material layer satisfies 0.0035 cm≦T2≦0.005 cm.
[0085] In these above-mentioned embodiments, by setting the thickness T2 of the negative electrode active material layer within the above-mentioned appropriate range, the resistance of the battery cell can be reduced, and the power performance of the battery cell can be improved, and the cycle performance of the battery cell can be improved.
[0086] In some examples, the thickness T2 of the negative electrode active material layer can be, but is not limited to, 0.003 cm, 0.0031 cm, 0.0032 cm, 0.0033 cm, 0.0034 cm, 0.0035 cm, 0.0036 cm, 0.0037 cm, 0.0038 cm, 0.0039 cm, 0.0040 cm, 0.0041 cm, 0.0042 cm, 0.0043 cm, 0.0044 cm, 0.0045 cm, 0.0046 cm, 0.0047 cm, 0.0048 cm, 0.0049 cm, or 0.0050 cm.
[0087] In some embodiments of the present application, the porosity P2 of the negative electrode active material layer satisfies 30%≦P2≦60%.
[0088] In these above embodiments, the porosity P2 of the negative electrode active material layer is set to the above appropriate range, which is favorable for the transmission of ions in the negative electrode active material, and can further reduce the resistance of the battery cell and improve the power performance of the battery cell.
[0089] In some other embodiments of the present application, the porosity P2 of the negative electrode active material layer satisfies 40%≦P2≦60%.
[0090] In these above embodiments, the porosity P2 of the negative electrode active material layer is set within the above appropriate range, so that the transmission speed of ions in the negative electrode active material layer can be further increased, and the power performance of the battery cell can be further improved.
[0091] In some examples, the porosity P2 of the negative electrode active material layer may be, but is not limited to, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, or 60%.
[0092] In some embodiments of the present application, the negative electrode active material layer has a BET specific surface area S2 of 1.7 m 2 / g≦S2≦2.2m 2 / g.
[0093] In these above embodiments, the BET specific surface area S2 of the negative electrode active material is set to the above appropriate range, so that the ion transmission speed in the negative electrode active material layer can be increased, and the power performance of the battery cell can be further improved.
[0094] In some embodiments of the present application, the negative electrode active material is natural graphite, artificial graphite, mesocarbon microbeads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithiated TiO2-Li4Ti5O with spinel structure. 12 , Li-Al alloys, or combinations thereof.
[0095] In addition, in some embodiments of the present application, the negative electrode active material layer may further include a conductive agent and an adhesive. The embodiments of the present application do not specifically limit the types of the conductive agent and adhesive in the negative electrode active material layer, and may be selected according to actual requirements.
[0096] For example, the conductive agent may be one or more of, but is not limited to, graphite, superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The adhesive may be one or more of, but is not limited to, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin, and carboxymethyl cellulose (CMC).
[0097] In some embodiments of the present application, the negative electrode current collector can be made of a material such as a metal foil or a porous metal plate. For example, the material of the negative electrode current collector can be, but is not limited to, a foil or a porous plate of a metal such as copper, nickel, titanium, or iron, or an alloy thereof. Furthermore, in some specific embodiments of the present application, the negative electrode current collector is made of copper foil.
[0098] The negative electrode plate of the present embodiment can be manufactured by a method commonly used in the art. For example, a negative electrode active material, a conductive agent, an adhesive, and a thickener are dispersed in an appropriate amount of ion-exchanged water at a certain mass ratio, and a pore-forming agent is added and thoroughly stirred to form a uniformly dispersed negative electrode slurry. The negative electrode slurry is applied to the surface of the copper foil of a negative electrode current collector, and then dried, cold-pressed, and cut to obtain a negative electrode plate.
[0099] In some embodiments of the present application, the thickness T3 of the separator satisfies 0.0005 cm≦T3≦0.0015 cm.
[0100] In these above-mentioned embodiments, by setting the thickness T3 of the separator within the above-mentioned range, the transmission path of ions in the separator can be shortened, the resistance of the battery cell can be further reduced, and the power performance can be improved.
[0101] In some examples, the separator thickness T3 may be, but is not limited to, 0.0005 cm, 0.0006 cm, 0.0007 cm, 0.0008 cm, 0.0009 cm, 0.0010 cm, 0.0011 cm, 0.0012 cm, 0.0013 cm, 0.0014 cm, or 0.0015 cm.
[0102] In some embodiments of the present application, the porosity P3 of the separator satisfies 30%≦P3≦80%.
[0103] In these above-mentioned embodiments, the porosity P3 of the separator is set within the above-mentioned range, which is favorable for ion transmission, and can increase the ion transmission speed, and further reduce the resistance of the battery cell, thereby improving the power performance of the battery cell.
[0104] In some examples, the porosity P3 of the separator may be, but is not limited to, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, or 80%.
[0105] In some embodiments of the present application, the separator has an air permeability of 150s / 100cm 3 That's all.
[0106] In the present application, there is no particular limitation on the method for measuring the air permeability of the separator. The air permeability can be measured by a method commonly used in the art. A non-limiting example of the method for measuring the air permeability is as follows. In an environment with a temperature of 15°C to 28°C and a humidity of less than 80%, a test sample was cut to a size of 4 cm x 4 cm, and measured using an air permeability tester according to the Gurley test (100 cc) method to directly obtain the air permeability value.
[0107] In these above-mentioned embodiments, the separator air permeability is set within the above-mentioned range, which is favorable for ion transmission and can increase the ion transmission speed, thereby further reducing the resistance of the battery cell and improving the power performance of the battery cell.
[0108] In some embodiments of the present application, the separator may be selected from polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), Kevlar, polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyimide (PI), polyamide, polyester, and natural fibers, or combinations thereof.
[0109] In some embodiments of the present application, the ionic conductivity G of the electrolyte at 25° C. satisfies 13 mS / cm≦G≦26 mS / cm.
[0110] In these above-mentioned examples, by setting the ionic conductivity G of the electrolyte at 25°C within the above-mentioned appropriate range, the conductive ability of ions in the electrolyte can be strengthened, the resistance of the battery cell can be further reduced, and the power performance of the battery cell can be further improved.
[0111] In some other embodiments of the present application, the ionic conductivity G of the electrolyte at 25° C. satisfies 14 mS / cm≦G≦25 mS / cm.
[0112] In these above embodiments, the ion conducting ability in the electrolyte can be further enhanced, so that the resistance of the battery cell can be further reduced and the power performance of the battery cell can be further improved.
[0113] In some examples, the ionic conductivity G of the electrolyte at 25° C. can be, but is not limited to, 13 mS / cm, 14 mS / cm, 15 mS / cm, 16 mS / cm, 17 mS / cm, 18 mS / cm, 19 mS / cm, 20 mS / cm, 21 mS / cm, 22 mS / cm, 23 mS / cm, 24 mS / cm, 25 mS / cm, or 26 mS / cm.
[0114] In some embodiments of the present application, the electrolyte retention rate N satisfies 3 g / Ah≦N≦7 g / Ah.
[0115] In the present application, the electrolyte retention rate N is the ratio of the amount of electrolyte retained to the first cycle discharge capacity of the battery cell.
[0116] In these above-mentioned examples, by setting the electrolyte retention rate N within the above-mentioned range, the resistance of the battery cell can be reduced, thereby improving the power performance of the battery cell and further improving the cycle performance of the battery cell.
[0117] In some examples, the electrolyte retention rate N may be, but is not limited to, 3 g / Ah, 4 g / Ah, 5 g / Ah, 6 g / Ah, 7 g / Ah.
[0118] In some embodiments of the present application, the electrolyte solution includes an electrolyte salt and an organic compound having a viscosity μ of 0.1 mPa·s to 3.5 mPa·s.
[0119] In the above examples, the viscosity of the organic compound can be tested by referring to GB / T 10247-2008 "Method of Viscosity Measurement". In particular, the viscosity was tested using a Brookfield (DV-2TLV) viscometer with a No. 18 rotor at about 70 r / min. The electrolyte contains an electrolyte salt and an organic compound whose viscosity μ satisfies the above relationship, so that the electrolyte has high conductivity, which can further reduce the resistance of the battery cell and further improve the power performance of the battery cell.
[0120] In some embodiments of the present application, based on the mass of the electrolyte solution, the mass fraction A of the electrolyte salt satisfies 10%≦A≦20%, and the mass fraction B of the organic compound satisfies 30%≦B≦70%.
[0121] In these above-mentioned examples, by setting the mass fraction A of the electrolyte salt and the mass fraction B of the organic compound within the above-mentioned appropriate ranges, respectively, it is possible to reduce the viscosity of the electrolyte solution, improve the conductivity of the electrolyte solution, further reduce the resistance of the battery cell, and further improve the resistance of the battery cell.
[0122] In some embodiments herein, the electrolyte salt comprises a lithium salt.
[0123] In some specific embodiments of the present application, the lithium salt is selected from lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), or a combination thereof.
[0124] In some embodiments herein, the organic compound includes a sulfone-based organic compound, an ether-based organic compound, an ester-based organic compound, and a nitrile-based organic compound, or a combination thereof.
[0125] For example, the sulfone organic compound is selected from dimethyl sulfoxide (DMSO), the ether organic compound is selected from ethylene glycol dimethyl ether (DME), the ester organic compound is selected from methyl formate (MF), ethyl formate, methyl acetate (MA), ethyl acetate (EA), methyl acrylate, or a combination thereof, and the nitrile organic compound is selected from acetonitrile (AN).
[0126] In some embodiments of the present application, the electrolyte further comprises a high temperature additive, the mass fraction C of the high temperature additive being 0.01%≦C≦1%, based on the mass of the electrolyte.
[0127] In the above embodiments, the high temperature additive and its content can contribute to forming a protective layer on the surface of the plate, which can be stable under high temperature conditions and is beneficial for protecting the plate, so that the battery cell can have good high temperature performance.
[0128] In some embodiments of the present application, the high temperature additive is selected from lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium fluorosulfonate (LiFSO3), lithium sulfamate (LiH2NO3S), or a combination thereof. The high temperature additive contributes to the formation of an inorganic protective layer, which can improve the mechanical strength of the protective layer and further improve the high temperature performance of the battery.
[0129] In some embodiments of the present application, the electrolyte further comprises a film-forming additive, the mass fraction D of the film-forming additive satisfying 1%≦D≦5% based on the mass of the electrolyte.
[0130] In these above examples, the film-forming additive and its content contribute to improving the stability of the interfacial film, and can improve the cycle performance of the battery cell.
[0131] In some embodiments herein, the film-forming additive is selected from vinylene carbonate, fluorinated ethylene carbonate, vinyl ethylene carbonate, or combinations thereof.
[0132] FIG. 4 shows an example of a battery cell, and FIG. 5 shows an exploded view of the battery cell in FIG.
[0133] 4 and 5, the battery cell 20 includes a case 21, an electrode assembly 22, and a cover assembly 23. The case 21 has a chamber for accommodating the electrode assembly 22, and the cover assembly 23 is used to close the opening of the case 21. The cover assembly 23 includes end caps, which are connected to the case 21 to form a housing for the battery cell 20, the electrode assembly 22 is disposed in the case 21, and the case 21 is filled with an electrolyte.
[0134] The end cap is a member that engages with the opening of the case 21 to isolate the internal environment of the battery cell 20 from the external environment. Although not limited thereto, the shape of the end cap can be adapted to the shape of the case 21 to be fitted to the case 21. Optionally, the end cap may be made of a material (e.g., aluminum alloy) having a certain hardness and strength. In this way, the end cap is less likely to be distorted when pressed and hit, and the battery cell 20 can have higher structural strength and improve safety performance. The end cap may be provided with a functional member such as an electrode terminal. The electrode terminal may be used to electrically connect with the electrode assembly 22 to output or input electrical energy of the battery cell 20. In some embodiments, the end cap may further be provided with a pressure release mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold value. The material of the end cap may be of multiple types, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc. The embodiments of the present application are not particularly limited thereto. In some embodiments, an insulating assembly may be further provided inside the end cap to isolate the electrical connection members in the case 21 from the end cap to reduce the risk of short circuit. For example, the insulating assembly may be plastic, rubber, etc.
[0135] The case 21 is an assembly for forming an internal environment of the battery cell 20 together with the end cap. In particular, the formed internal environment may be used to accommodate the electrode assembly 22, the electrolyte, and other components. The case 21 and the end cap may be independent components, and an opening may be provided in the case 21, and the end cap may be engaged with the opening to form the internal environment of the battery cell 20. The end cap and the case 21 may be integrated, but are not limited to these. Specifically, the end cap and the case 21 may form a common connection surface before other components are inserted into the case, and when it is necessary to seal the inside of the case 21, the end cap is engaged with the case 21. The case 21 may have a variety of shapes and sizes, such as a rectangular parallelepiped, a cylindrical body, a hexagonal prism, and the like.
[0136] The electrode assembly 22 is a component that generates an electrochemical reaction in the battery cell 20. The case 21 may include one or more electrode assemblies 22. The electrode assembly 22 is mainly formed by winding or stacking a positive electrode plate and a negative electrode plate, and a separator is usually provided between the positive electrode plate and the negative electrode plate. The parts of the positive electrode plate and the negative electrode plate that have active materials form the main body of the electrode assembly 22, and the parts that do not have active materials form tabs. The positive electrode tab and the negative electrode tab can be jointly located at one end of the main body, or can be located at both ends of the main body. During the charging and discharging process of the battery, the positive electrode active material and the negative electrode active material react with the electrolyte, and the tabs are connected to the electrode terminals to form a current circuit.
[0137] The battery cell provided in the embodiment of the present application can be manufactured by a conventional method. For example, the following manufacturing method can be used. A positive electrode active material, a conductive agent, and an adhesive are dispersed in a solvent (e.g., N-methylpyrrolidone, abbreviated as NMP) to form a uniform positive electrode slurry, and the positive electrode slurry is applied to two opposing surfaces of a positive electrode current collector, and then dried, cold pressed, and cut to obtain a positive electrode plate. A negative electrode active material, a conductive agent, an adhesive, and a thickener are dispersed in a solvent (e.g., ion-exchanged water), a pore-forming agent is added, and the mixture is stirred to obtain a uniformly dispersed negative electrode slurry, and the negative electrode slurry is applied to two opposing surfaces of a negative electrode current collector, and then dried, cold pressed, and cut to obtain a negative electrode plate. A positive electrode plate, a separator, and a negative electrode plate are stacked in order to obtain an electrode assembly, or are stacked in order and wound up to obtain an electrode assembly. The electrode assembly was placed in a case, an electrolyte was injected and sealed, the case was injected with an electrolyte and sealed, and the assembly was left standing at high temperature, subjected to formation and grading, and then a battery cell was obtained.
[0138] The following examples will more specifically describe the contents disclosed in the present application, but these examples are merely for illustrative purposes, and it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. All reagents used in the examples can be obtained commercially or synthesized by conventional methods, and can be used as is without further treatment, and all instruments used in the examples can be obtained commercially. Example 1
[0139] Positive electrode plate manufacturing
[0140] Lithium iron phosphate (LFP) with an olivine structure, polyvinylidene fluoride (PVDF), and carbon black (SP) were mixed with a solvent in a mass ratio of 97:2:1, and stirred to obtain a uniformly dispersed positive electrode slurry. The positive electrode slurry was then evenly applied to two surfaces of aluminum foil, which was then dried, cold pressed, and cut to obtain a positive electrode plate.
[0141] Negative plate manufacturing
[0142] Artificial graphite, carbon black (SP), styrene butadiene rubber (SBR), and sodium hydroxymethylcellulose (CMC) were mixed with a solvent in a ratio of 97:0.5:1.5:1, a pore-forming agent was added, and the mixture was stirred to obtain a uniformly dispersed negative electrode slurry. The negative electrode slurry was then evenly applied to the two surfaces of copper foil, which was then dried, cold pressed, and cut to obtain a negative electrode plate.
[0143] Electrolyte production
[0144] In a glove box with an argon gas atmosphere (H2O<0.1ppm, O2<0.1ppm), 30% ethylene carbonate (EC), 15% dimethyl carbonate (DMC), 40% ethylene glycol dimethyl ether (DME), and 15% lithium hexafluorophosphate (LiPF6) were mixed by mass fraction to obtain an electrolyte.
[0145] Separator
[0146] A polyethylene film served as the separator.
[0147] Battery cell manufacturing:
[0148] The positive electrode plate, the negative electrode plate and the separator are fabricated into an electrode assembly by a winding process or a lamination process, and then placed into a case made of an aluminum housing, an aluminum plastic film or the like. The case is then filled with an electrolyte and sealed. After being left to stand at high temperature, formation and grading are performed, and a battery cell is obtained.
[0149] Examples 2 to 28 and Comparative Example 1
[0150] The manufacturing methods of Examples 2 to 28 and Comparative Example 1 were the same as those of Example 1, and differences are shown in Tables 1 and 2.
[0151] Testing part
[0152] (1) T1, T2 and T3 tests
[0153] The battery cell was discharged to 2.5V at a rate of 0.1C, and then disassembled to obtain the positive plate, negative plate, and separator. The positive plate, negative plate, and separator were left at room temperature in a dry environment (humidity ≦2%) for 24 hours until the electrolyte evaporated, and the broken positive plate was taken out and the thickness of the positive plate at the middle was measured with a screw micrometer. The thickness was then measured at the next point by shifting the position, and the thickness data of 50 points was collected, the average value T1' was obtained, and the thickness T0 of the current collector was measured at the same time. When the positive plate was coated on one side, T1=T1'-T0, and when the positive plate was coated on both sides, T1=(T1'-T0) / 2. The measurement method of T2 was the same as that of T1.
[0154] The separator with the broken middle was taken, and the thickness of the separator at the middle position was measured with a screw micrometer, and then the separator was shifted and the next point was measured, and thickness data was collected at 50 points to obtain the average value T3.
[0155] (2) Tests P1, P2 and P3
[0156] Tested according to the method of GB / T 24586-2009.
[0157] (3) G test
[0158] The ionic conductivity of the electrolyte was tested using a REX conductivity meter at 25°C.
[0159] (4) BET specific surface area test
[0160] As a result of testing with reference to GB / T 19587-2004 "Measurement of the specific surface area of solids by gas adsorption BET method", the BET: 10 m 2 / g, BET of negative plate: 1.9m 2 / g.
[0161] (5) Air permeability test
[0162] In an environment with a temperature of 15°C to 28°C and a humidity of less than 80%, the test sample was cut to a size of 4 cm x 4 cm and measured using an air permeability tester by the Gurley test (100 cc) method to obtain a direct air permeability value. As a result of the test, the air permeability of each example and comparative example was 150s / 100cm 3 It was.
[0163] (6) 10C discharge capacity retention test
[0164] At room temperature of 25°C ± 2°C, the battery cell was charged to 3.65V at a constant current of 0.3C, charged at a constant voltage until the current became 0.05C, and left to stand for 10 min. The battery cell was discharged from a constant current of 0.3C to 2.5V, and the discharge capacity was recorded as D1. The battery cell was then charged to 3.65V at a constant current of 0.3C, charged at a constant voltage until the current became 0.05C, and left to stand for 10 min. The battery cell was discharged to 2.5V at a constant current of 10C, and the discharge capacity was recorded as D2. The discharge capacity retention rate at 10C was = D2 / D1.
[0165] (7) Capacity retention test
[0166] At room temperature of 25°C ± 2°C, the battery cell was charged to 3.65V at a constant current of 5C, charged at a constant voltage until the current became 0.05C, and left to stand for 10 minutes. It was discharged to 2.5V at a constant current of 3C, the discharge capacity was recorded as Q1, and left to stand for 10 minutes. The above steps were repeated 500 times, and the final discharge capacity Q2 was recorded, and the capacity retention rate of the battery cell = Q2 / Q1.
[0167] (8) Liquid retention rate N test
[0168] The battery cell to be disassembled was weighed to obtain M1. The battery cell was disassembled, the free electrolyte was discarded, dimethyl carbonate (DMC) was added to the case and extracted three times, the remaining DMC liquid was discarded, the electrode assembly and the case were placed in an oven to thoroughly remove the DMC, and the battery was weighed to obtain M2. The amount of electrolyte retention was M1-M2, and the electrolyte retention rate N was (M1-M2) / Q1.
[0169] Tables 1 and 2 list some of the parameters of the battery cells of Examples 1 to 28 and Comparative Example 1, respectively. Among them, Z in Table 1 is
number
[0170] [Table 1-1] [Table 1-2]
[0171] [Table 2-1] [Table 2-2]
[0172] [Table 3]
[0173] As can be seen from Table 1, in the battery cell provided by the embodiments of the present application, the thickness T1 and porosity P1 of the positive electrode active material layer, the thickness T2 and porosity P2 of the negative electrode active material layer, the thickness T3 and porosity P3 of the separator, and the ionic conductivity G of the electrolyte all satisfy the above relationships, so that the battery cell has low resistance at a high rate, and further improves the power performance of the battery cell, thereby achieving both the rate performance and power performance of the battery cell.
[0174] Although the present application has been described with reference to the preferred embodiments, various improvements can be made thereto and equivalents can be substituted for the elements therein without departing from the scope of the present application. Each technical feature mentioned in each embodiment can be combined in any manner unless there is a particular structural discrepancy. The present application is not limited to the specific embodiments disclosed in the specification, but includes all embodiments falling within the scope of the claims.
Claims
1. A positive electrode plate including a positive electrode current collector and a positive electrode active material layer provided on at least one side of the positive electrode current collector; a negative electrode plate including a negative electrode current collector and a negative electrode active material layer provided on at least one side of the negative electrode current collector; A separator provided between the positive electrode plate and the negative electrode plate; and an electrolyte. The positive electrode active material layer, the negative electrode active material layer, the separator, and the electrolyte satisfy the following relationship: [0045] Wherein, T1 is the thickness of the positive electrode active material layer, in cm; P1 is the porosity of the positive electrode active material layer; T2 is the thickness of the negative electrode active material layer in cm; P2 is the porosity of the negative electrode active material layer; T3 is the thickness of the separator in cm; P3 is the porosity of the separator; G is the ionic conductivity of the electrolyte at 25° C., in mS / cm; A battery cell characterized by:
2. The thickness T1 of the positive electrode active material layer satisfies 0.0035 cm≦T1≦0.0055 cm, and optionally satisfies 0.0035 cm≦T1≦0.0045 cm; The battery cell according to claim 1 .
3. The porosity P1 of the positive electrode active material layer satisfies 30%≦P1≦60%, and optionally satisfies 40%≦P1≦60%; 3. The battery cell according to claim 1 or 2.
4. The positive electrode active material layer has a BET specific surface area S1 of 8 m 2 / g≦S1≦12m 2 / g, The battery cell according to any one of claims 1 to 3.
5. the thickness T2 of the negative electrode active material layer satisfies 0.003 cm≦T2≦0.005 cm, and optionally satisfies 0.0035 cm≦T2≦0.005 cm; The battery cell according to any one of claims 1 to 4.
6. The porosity P2 of the negative electrode active material layer satisfies 30%≦P2≦60%, and optionally satisfies 40%≦P2≦60%; The battery cell according to any one of claims 1 to 5.
7. The negative electrode active material layer has a BET specific surface area S2 of 1.7 m 2 / g≦S2≦2.2m 2 / g, The battery cell according to any one of claims 1 to 6.
8. The thickness T3 of the separator satisfies 0.0005 cm≦T3≦0.0015 cm. The battery cell according to any one of claims 1 to 7.
9. The porosity P3 of the separator satisfies 30%≦P3≦80%. The battery cell according to any one of claims 1 to 8.
10. The separator has an air permeability of 150s / 100cm 3 That's all. The battery cell according to any one of claims 1 to 9.
11. The ionic conductivity G of the electrolyte at 25° C. satisfies 13 mS / cm≦G≦26 mS / cm, and optionally satisfies 14 mS / cm≦G≦25 mS / cm; The battery cell according to any one of claims 1 to 10.
12. The electrolyte retention rate N satisfies 3 g / Ah≦N≦7 g / Ah, The battery cell according to any one of claims 1 to 11.
13. The electrolytic solution contains an electrolyte salt and an organic compound having a viscosity μ of 0.1 mPa·s to 3.5 mPa·s. The battery cell according to any one of claims 1 to 12.
14. Based on the mass of the electrolytic solution, a mass fraction A of the electrolyte salt satisfies 10%≦A≦20%, and a mass fraction B of the organic compound satisfies 30%≦B≦70%. The battery cell according to claim 13 .
15. the electrolyte salt comprises a lithium salt; Optionally, the lithium salt is selected from lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide, or a combination thereof; 15. The battery cell according to claim 13 or 14.
16. The organic compound includes a sulfone-based organic compound, an ether-based organic compound, an ester-based organic compound, and a nitrile-based organic compound; Optionally, the sulfonic organic compound is selected from dimethyl sulfoxide; Optionally, the ether-based organic compound is selected from ethylene glycol dimethyl ether; Optionally, the ester-based organic compound is selected from methyl formate, ethyl formate, methyl acetate, ethyl acetate, methyl acrylate, or a combination thereof; Optionally, the nitrile organic compound is selected from acetonitrile; The battery cell according to any one of claims 13 to 15.
17. The electrolyte further includes a high temperature additive, and based on the mass of the electrolyte, the mass fraction C of the high temperature additive satisfies 0.01%≦C≦1%; The battery cell according to any one of claims 11 to 16.
18. The high temperature additive is selected from lithium tetrafluoroborate, lithium difluorophosphate, lithium fluorosulfonate, lithium sulfamate, or combinations thereof; 20. The battery cell of claim 17 .
19. The electrolytic solution further includes a film-forming additive, and a mass fraction D of the film-forming additive satisfies 1%≦D≦5% based on the mass of the electrolytic solution; The battery cell according to any one of claims 11 to 18.
20. The film-forming additive is selected from vinylene carbonate, fluorinated ethylene carbonate, vinyl ethylene carbonate, or a combination thereof; 20. The battery cell of claim 19.
21. A battery cell comprising the battery cell according to any one of claims 1 to 20. A battery characterized in that
22. A battery cell according to any one of claims 1 to 20, or a battery according to claim 21.
1. An electrical device comprising:
Citation Information
Patent Citations
Battery
JP2000268794A
Nonaqueous electrolyte battery
JP2011096643A
Electrical equipment
JP2012069722A
Non-aqueous secondary battery
WO2013062056A1
Paste composition, electrode material for secondary batteries, electrode for secondary batteries, and secondary battery
WO2020071056A1